Quasi-experimental evaluation of a financial incentive for first-dose COVID-19 vaccination among adults aged ≥60 years in South Africa. Issue 12 (21st December 2022) - Chetty-Makkan, Candice Maylene; Thirumurthy, Harsha; Bair, Elizabeth F; Bokolo, Simamkele; Day, Candy; Wapenaar, Korstiaan; Werner, Jesse; Long, Lawrence; Maughan-Brown, Brendan; Miot, Jacqui; Pascoe, Sophie J S; Buttenheim, Alison M
Abstract : Introduction: COVID-19 vaccination coverage in South Africa (RSA) remains low despite increased access to vaccines. On 1 November 2021, RSA introduced the Vooma Voucher programme which provided a small guaranteed financial incentive, a Vooma Voucher redeemable at grocery stores, for COVID-19 vaccination among older adults, a population most vulnerable to serious illness, hospitalisation and death. However, the association of financial incentives with vaccination coverage remains unclear. Methods: We evaluated the association of the conditional economic incentive programme with first-dose vaccination rates among adults (aged ≥60 years) through a quasi-experimental cohort study. The Vooma Voucher programme was a nationwide vaccination incentive programme implemented for adults aged ≥60 years from 1 November 2021 to 28 February 2022. We ran ITS models to evaluate the Vooma Voucher programme at national and provincial levels. We used data between 1 October 2021 and 27 November 2021 in models estimated at the daily level. Individuals who received their first vaccine dose received a text message to access a ZAR100 ( 7) voucher that was redeemable at grocery stores. Results: The Vooma Voucher programme was associated with a 7.15%–12.01% increase in daily first-dose vaccinations in November 2021 compared with late October 2021. Overall, the incentive accounted for 6476–10 874 additional first vaccine doses from 1 November to 27 November 2021, or 8.31%–13.95% of all doses administered to those aged ≥60 years during that period. This result is robust to the inclusion of controls for the number of active vaccine delivery sites and for the nationwide Vooma vaccination weekend initiative (12 November to 14 November), both of which also increased vaccinations through expanded access to vaccines and demand creation activities. Conclusions: Financial incentives for COVID-19 vaccination led to a modest increase in first-dose vaccinations among older adults in RSA. Financial incentives and expanded access to vaccines may result in higher vaccination coverage. Trial registration number (SANCTR): DOH-27-012022-9116.